Climate action for food security in South Asia? Analyzing the role of agriculture in nationally determined contributions to the Paris agreement - Amjath-Babu, Tharayil Shereef; Aggarwal, Pramod K.; Vermeulen, Sonja J. (Informa UK Limited, 2019)
The Nationally Determined Contributions (NDCs) submitted under the Paris Agreement propose a country’s contribution to global mitigation efforts and domestic adaptation initiatives. This paper provides a systematic analysis of NDCs submitted by South Asian nations, in order to assess how far their commitments might deliver meaningful contributions to the global 2°C target and to sustainable broad-based adaptation benefits. Though agriculture-related emissions are prominent in emission profiles of South Asian countries, their emission reduction commitments are less likely to include agriculture, partly because of a concern over food security. We find that income-enhancing mitigation technologies that do not jeopardize food security may significantly augment the region’s mitigation potential. In the case of adaptation, analysis shows that the greatest effort will be directed towards protecting the cornerstones of the ‘green revolution’ for ensuring food security. Development of efficient and climate-resilient agricultural value chains and integrated farming bodies will be important to ensuring adaptation investment. Potentially useful models of landscape level climate resilience actions and ecosystem-based adaptation are also presented, along with estimates of the aggregate costs of agricultural adaptation. Countries in the region propose different mixes of domestic and foreign, and public and private, adaptation finance to meet the substantial gaps.